Whether God Exists Is Irrelevant to Ethics - David Kyle Johnson (Religions)
The question of whether ethics is possible without God is a non-issue. While many believe that without God, morality collapses, I contend that the existence or non-existence of God has no bearing on whether ethics is possible, whether moral truths exist, or whether ethical inquiry is viable. Ethics is no more secure within a theistic framework than an atheistic one. I establish this by critically examining Divine Command Theory (DCT) and its variants, including Divine Nature Theory, demonstrating that they fail to provide truthmakers for moral statements, explain moral truths, generate moral knowledge, or serve as a practical guide for ethical decision making. If one seeks a way to justify ethical principles or resolve moral dilemmas, appealing to God does not improve the situation; supernatural explanations, including those invoking divine commands or nature, fail to meet the criteria of explanatory adequacy. I conclude by suggesting a secular approach to ethics—drawing from Ted Schick’s inference to the best action—that does not depend on God’s existence. Ultimately, if moral nihilism is a concern, God’s existence offers no solution. If ethics is possible at all, it is possible regardless of whether God exists.